Xorides xylotrechi sp. n. (Hymenoptera: Ichneumonidae: Xoridinae) parasitizing Xylotrechus stebbingi (Gahan, 1906) (Coleoptera: Cerambycidae) in India - Maqbool, Iqra; Varga, Oleksandr; Maqbool, Amir; Wachkoo, Aijaz Ahmad; Banu, A. Najitha; Rather, Sumi Ulah (Zootaxa, 2022)
New xoridine species, Xorides xylotrechi sp. n., from India is described and illustrated. The parasitoid was reared from the larvae of the xylophagous beetle, Xylotrechus stebbingi (Gahan, 1906), infesting Juglans regia L. Notes on parasitoid behaviour and biology are also provided with a brief description of female reproductive system and venom apparatus.